Co-localization of ribosomal and telomeric sequences in Leptynia (Insecta: Phasmatodea). Issue 3 (2nd July 2016) - Scali, V.; Coluccia, E.; Deidda, F.; Lobina, C.; Deiana, A. M.; Salvadori, S.
Abstract: Stick insects have been studied mainly for non-conventional reproduction modes, such as parthenogenesis, hybridogenesis and androgenesis. Parallel karyological investigations have evidenced extensive numerical and structural chromosome re-patterning, particularly evident in hybrid parthenogenetic taxa. Chromosome sets of bisexual Leptynia (Pantel) species show an evolutionary trend from 40 to 36 chromosomes and are characterized by cytological satellites of variable size and localization. We performed fluorescence in situ hybridization (FISH) analysis using 45S ribosomal genes and pentameric (TTAGG)n telomere sequences as probes in two strictly related but karyotypically distinct species, L. montana Scali (2n = 38/37; XX/XO) and L. attenuata Pantel (2n = 36). L. attenuata has recently been split into three subspecies ( L. attenuata attenuata, L. attenuata iberica and L. attenuata algarvica ), and found to share an XX/XY sex chromosome formula, unusual for stick insects. FISH by 45S rDNA sequences consistently labelled the short arm of the 4th chromosome pair, often of a variable size. Silver staining showed that nucleolar organizer regions (NORs) are active. FISH of the telomeric repeats, besides ordinary telomeres, also labelled the short arm of this same pair. The use of both probes in double FISH analysis fully confirmed the co-localization of ribosomal and telomeric highly repeated sequences. Since it is increasingly emerging that the co-localization of NORs and telomeric sequences appears to be a feature shared by evolutionarily distant animals, its possible role is discussed.